Transnational moralities: the politics of ir/responsibility of and against the EU border regime. Issue 5 (3rd September 2018) - Perl, Gerhild; Strasser, Sabine
ABSTRACT: The death of Alan Kurdi, the boy washed ashore in Turkey in September 2015, provoked a global moral outcry. The pictures of the toddler went viral across social networks and in the media. Following these images across borders, we analyse moral and political responses to the 'EU refugee crisis' by illuminating the circumstances under which people feel, take on, and demand responsibility. Considering EU policies and their lethal consequences as mechanisms of an organised irresponsibility, we show how the circulation and modification of the images played on moral sentiments and on political demands in Europe and across the Mediterranean. The anthropological engagement with transnational moralities contributes to the analysis of politics of ir/responsibility of and against the EU border regime.